Processes of salt slag recycling in aluminum production to obtain powder material with a high content of aluminum oxide phases - B. M. Nemenenok; I. V. Rafalski; P. E. Lushchik; L. P. Dolgi; A. D. Rulenkov (Литьë и металлургия, 2023)
The processing of salt slags in aluminum production in order to obtain a powder material with a high content of aluminum oxide phases and the results of thermodynamic assessment of the hydrolysis reactions of aluminum carbide and nitride during the hydraulic treatment of slags are discussed. It is reported that water‑soluble fluorine compounds, such as Na3AlF6, CaF2, MgF2, K2ZrF6 , in the composition of refining fluxes complicates the processing of aluminum slags, which involve leaching of salts by water. A rational solution seems to be the replacement of sparingly soluble salts in refining fluxes with sodium or potassium fluorides with a higher solubility in water. It is shown that the powder mixture obtained after hydraulic treatment of aluminum slag includes various forms of structural components in the form of films, shells, submicroand nanostructures of various morphologies with the participation of various types of nano‑components, in which the phases of non‑metallic compounds predominate, mainly ceramic substances and salts (corundum Al2O3, aluminum oxynitride Al2.85O3.45N0.55, aluminum nitride AlN, sodium chloride NaCl) and metallic aluminum. It is indicated that the possibility of forming eutectic mixtures of ceramic compounds of aluminum oxide and aluminum oxynitride, which are more fusible than pure oxides and nitrides, must be taken into account when developing salt slag recycling technologies in order to obtain ceramic powder materials with a high content of alumina phases.